Prevalence of depression, anxiety and stress among jail inmates - Malik, J. S.; Singh, Paritev; Beniwal, Meenu; Kumar, Tarun (International Journal Of Community Medicine And Public Health, 2019)
Background: There are about 1387 prisons in the country with an authorized accommodation of 356,561; however, the total number of jail inmates is 418536 indicating severe overcrowding in prisons. Prison population is an underserved section of the society. Often their health problems are neglected. They carry a much greater burden of illness than other members of the society; they harbour diseases that are determined both by the environment out of which they come and by the prison in which they live. Therefore, present study was conducted with the aim of studying the mental health status of persons from a section of our society, who were condemned by law and are behind the high walls. Methods: A cross sectional study was carried out on 400 convicted inmates in district jail, Rohtak, Haryana over the period of one and half years. Data was collected by interview method using DASS-21 scale and analysed by SPSS 20.0 and Chi square test was applied for results. Results: The prevalence of depression came out to be 18.5%, anxiety came out to be 8% and stress was found to be prevalent in 8% of the convicted inmates confined in jail which was much higher in comparison to general population. Conclusions: As the prevalence of depression, stress and anxiety was found much higher in convicts than the general population, there should be a timely screening, diagnosis and appropriate intervention to combat the mental health problems.